Democracia, direitos humanos, gênero e cidadania teoria, políticas e cotidiano das escolas públicas - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2022)
The academic vision contained in this book is singular and, at the same time, multicentric because it goes beyond the limits of scientific work and reveals contents of gender reality in historical, social, political, economic, religious and, above all, educational contexts to discuss them in perspective of democratic ideals and human rights. The Brazilian democratic process is analyzed critically and reflectively in its genesis, from the feminist movement, towards gender equality, surpassing territorial limits ranging from local to national, which gives probative value to the book's content. Real emphasis is given to democracy and citizenship in educational policies to revisit the concept of school as a social and knowledge space for the culture of Human Rights and gender equality. In a more specific, but no less important, discussion on democracy, human rights, citizenship and gender in educational policies, the São Paulo public school environment and its organization are an integral part of it as a way of evaluating the advances and setbacks caused by political and governmental. Reports and knowledge about other Latin American countries, Portugal and Spain, are included as an extension of the discussion on democracy, human rights, citizenship and gender in educational policies that is enriched, especially, with the mediation proposals carried out in public schools in Valencia. MARIÂNGELA SPOTTI LOPES FUJITA